Agricultural innovation and environmental change on the floodplains of the Congo River. Issue 1 (8th July 2019) - Comptour, Marion; Cosiaux, Ariane; Coomes, Oliver T.; Bader, Jean‐Claude; Malaterre, Pierre‐Olivier; Yoka, Joseph; Caillon, Sophie; McKey, Doyle
Abstract : Climate‐driven environmental changes bring new risks but also opportunities to populations living along the world's major rivers. Based on ethnoecological fieldwork, in this paper we examine how people living in the cuvette centrale of the Congo basin have adopted flood‐recession agriculture on islands in the Congo River, taking advantage of a secular shift since the 1980s in the hydrological regime of the Congo River. Analyses of the hydrological data reveal that this shift decreased flood risk and significantly extended the growing season on the islands, long enough to enable cultivation of fast‐maturing varieties of manioc and other crops. Flood‐recession farming on islands in the river is today not only an important source of food, but also a source of income for women, who are primarily responsible for seasonal cultivation of fields during the low‐water season. Hydrological changes alone are insufficient to explain the adoption of the new agricultural practice; adoption also arose as a result of dynamic interactions among river fishing, trading, and broader socio‐economic forces. Climate‐change models project an increased frequency of extreme floods. Our results suggest that this change may limit island cultivation in the future. More generally, our findings point to the importance of looking beyond single‐factor, solely environmental explanations in studies of climate‐change adaptation. Abstract : This paper explores how people living in the Congo basin adopted flood‐recession agriculture on islands in the Congo River since the 1980s. This agricultural innovation was made possible by a shift in the hydrological regime of the Congo river and rose as a result of broader socio‐economic forces, among them demographic growth, economic crisis, and changes in fishing and trade activities.